Literature review: Paparan merkuri (Hg) pada anak stunting di area pertambangan emas - Aisyah Aisyah; Anang M. Legowo; Muflihatul Muniroh (Jurnal SAGO Gizi dan Kesehatan, 2024)
Background: Mercury (Hg) is used by small-scale gold miners to extract gold. Mercury waste is dangerous and toxic because it pollutes the environment and living creatures. Mercury can accumulate in the body through the food chain, air and air. Children who are exposed to mercury are associated with a risk of various health problems that can result in stunting.Objective: The aim of writing this literature review is to identify exposure to mercury (Hg) in stunted children.Method: This research is in the form of descriptive analysis. This research took the form of a literature review, article synthesis was carried out in a narrative manner as recommended by the PRISMA statement in selecting the articles found. The keywords used are stunting, exposure to mercury (Hg) and gold mining areas. Literature sources were obtained from the Scopus database, Google Scholar, PubMed Central and Science Direct. Inclusion criteria are stunting, exposure to mercury (Hg) and gold mining areas, full text, published in 2013-2023. Exclusion criteria are articles in the form of books and documents, reviews, meta-analysis and systematic reviews.Results: Results from the literature show that stunted children are exposed to mercury that comes from the environment due to gold mining. Urine samples of stunted children aged 0-59 months contain mercury above 7 μg/L, which is the threshold set by Human Biomonitoring (HBM).Conclusion: Stunted children aged 0-59 months who live in gold mining areas are exposed to mercury. The risk of mercury exposure to children can come from food, water and air.KeywordsGold Mining Area, Mercury Exposure, Stunting